HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATA DIKLAT MEKANIKA TEKNIKSISWA KELAS X PROGRAM KEAHLIAN DESAIN PEMODELAN INFORMASI BANGUNAN DI SMK NEGERI 1 SUMATERA BARAT - 2080-2086, Febri Doni Saputra (Universitas Negeri Padang, 2018)
This research was motivated by low learning result of mekanika teknik x grade students design building information program at SMK N I West Sumatera. The purpose to determine there was/wasn’t relationship of learning motivation with learning result to mekanika teknik x grade students desain building information program at SMK N I West Sumatera. Type of this research was descriptive correlational research. The population of this research was students of ten grade students desain building information program 2017/2018 academic year, it’s 31 students, because the population was less than 100 so the sample taken all members of the polulation called Total Sampling was 31 students. The variables in this research were learning motivation as dependent variable (X) and learning result of mechanical engineering as dependent variable (Y).based on the result of correlation analysis obtained r value 0.468 in the medium category and correlation meaning test obtained tcount 2.85 > ttable 2.045, so Ho was refused in this research.Keywords: relationship, learning motivation, learning outcome